2019
DOI: 10.1002/clc.23243
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolites mediate the effect of HbA1c on incident cardiovascular disease

Abstract: Background We aim to discover whether HbA1c affects incident cardiovascular disease (CVD) through regulating endogenous metabolites. Methods and Results Totally, 2019 plasma samples were analyzed by liquid chromatography‐quadrupole time‐of‐flight mass spectrometry. Logistic regression and linear regression were used to screen metabolites which were associated with both CVD and HbA1c. The VanderWeele's mediation approach was performed to assess the direct effect and indirect effect (IE) in the counterfactual mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…This may indicate that high-dose acrylamide could cause oxidative damage. It is well known that high levels of GLU contribute to oxidative stress, which causes oxidative damage and dysfunction of the vascular endothelium as an indicator in many vascular diseases in the early stage . Notably, our study found that the concentration of GLU in the serum increased in a dose-dependent manner, indicating abnormal GLU metabolism and a higher risk of diabetes.…”
Section: Discussionsupporting
confidence: 48%
“…This may indicate that high-dose acrylamide could cause oxidative damage. It is well known that high levels of GLU contribute to oxidative stress, which causes oxidative damage and dysfunction of the vascular endothelium as an indicator in many vascular diseases in the early stage . Notably, our study found that the concentration of GLU in the serum increased in a dose-dependent manner, indicating abnormal GLU metabolism and a higher risk of diabetes.…”
Section: Discussionsupporting
confidence: 48%
“…Consistent with previous studies, this result indicated that the alanine, aspartate, and glutamate metabolism pathway is one mechanism of lipid regulation. [ 68,69 ]…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, this result indicated that the alanine, aspartate, and glutamate metabolism pathway is one mechanism of lipid regulation. [68,69] It is well known that lipoic acid can serve as an essential enzyme cofactor for -ketoacid dehydrogenase complexes) and play a vital role in cellular energy metabolism. Previous clinical trials and meta-analysis demonstrated a favorable effect of the lipoic acid supplement on lipids regulation, [70,71] while the results are mildly contradictory to the decreased concentrate of R-lipoic acid www.advancedsciencenews.com www.mnf-journal.com observed in the oat group this time.…”
Section: Alanine Aspartate and Glutamate Metabolismmentioning
confidence: 99%
“…As important enzyme substrates and regulators, amino acids play important roles in many metabolic pathways, which contain important biochemical information reflecting the metabolic and functional state of the body and play important roles in the normal operation of the immune system and other organs (White and Newgard, 2019). Studies have shown that phenylalanine metabolic disorder is related to the aggravation of oxidative stress reactions, such as lipid peroxidation in the body (Dong et al, 2019). The oxidative stress reaction causes vascular endothelial oxidative damage and then leads to vascular endothelial dysfunction, which is an indicative response in the early stage of many cardiovascular diseases (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%